Analisis Kesulitan Siswa Dalam Pemecahan Masalah Matematis Pada Materi Sistem Persamaan Linear Dua Variabel Kelas VIII SMPN 1 Biru-Biru - Lenny Kharsima Br Sembiring; Ani Minarni (Education Achievement: Journal of Science and Research, 2023)
This study aims to determine the difficulties experienced by students and to determine the level of mathematical problem solving ability of grade VIII students of SMP N 1 Blue – Blue. In this study using qualitative descriptive method. The population in this study was the entire class VIII of SMP Negeri 1 Biru – Biru consisting of 6 classes whose total students were 183 students. while the sampling in this study was as suggested by the teacher, namely class VIII-1 whose number of students was 31 students where there were 3 subjects whose subjects were selected based on high, medium, and low ability levels. The material used in this study is the Two Variable Linear Equation System (SPLDV). As a research instrument, test result data is used in the form of essay tests on SPLDV material, where each question amounts to 3 questions and has been validated by mathematics lecturers. The results of the analysis obtained are based on written tests conducted in class VIII-1. Subjects who have a high level of ability are able to answer questions well and only experience slight obstacles in calculating operations, but can be corrected by these subjects, subjects who have a moderate level of ability are able to understand problems and determine variables but have difficulty translating problems into mathematical sentences, err in operations so that they are wrong in calculations. Subjects who have a low level of ability are able to understand problems and determine variables but are unable to understand problems on varied problems. The subject has not been able to sort the information on the problem, and the subject has difficulty identifying the information on the problem and the formulas used to create the mathematical model. The subject does not master the principle of operation of algebra. The subject has not been able to complete correctly, the subject made some mistakes and was not careful in calculations.